Development of Search‐and‐rescue Robots for Underground Coal Mine Applications. Issue 3 (27th February 2014) - Wang, Weidong; Dong, Wei; Su, Yanyu; Wu, Dongmei; Du, Zhijiang
<x xml:space="preserve">Abstract</x> Rescue missions after coal mine accidents are highly risky and sometimes impossible for rescuers to perform. To decrease the risk to rescuers, two generations of tracked mobile robots have been designed and developed to replace the rescuers. In this paper, we present the design iterations with experiments carried out in training sites for rescuers and in working coal mines, and we summarize the design and development experiences of the mobile robots for such rescue missions. In coal mine rescue robots, the explosion‐proof and waterproof designs are adapted to the explosive and wet environments, while the suspension systems are adapted to the unstructured working environments. The design and development experiences may provide a reference for designing and developing future mobile robot systems for coal mine accident rescue missions.